High-brightness piezoelectric mechanical luminescent material and preparation method and application thereof

By adopting Linbo3: 0.01PR, XZN materials, using high -temperature solid -phase method to preparation to solve the problem of the stability and repetition of existing piezoelectric inorganic mechanical luminous materials, realize high brightness, long -term storage and repeated mechanical luminous characteristics characteristics Essence

CN119351095AActive Publication Date: 2025-01-24GUILIN UNIV OF ELECTRONIC TECH

Patent Information

Application Number
CN202411476965.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-22
Publication Date
2025-01-24
Estimated Expiration
2044-10-22

AI Technical Summary

Technical Problem

The existing piezoelectric inorganic mechanical luminescent materials have problems such as low luminescence intensity, poor stability and poor repeatability, making it difficult to achieve high brightness, long-term storage and repeatable mechanical luminescent characteristics.

Method used

The chemical formula is Linbo3: 0.01PR, and XZN's high -brightness voltage mechanical luminous material is prepared by high temperature solid -phase method, and an appropriate amount of ZNO is added to improve the performance of the material.

Benefits of technology

It achieves high brightness, long-term storage and repeatable mechanoluminescence characteristics. The luminescence intensity is 100% higher than that of non-Zn doped samples. It still has mechanoluminescence emission after being placed in a dark room environment for 30 days, with good repeatability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119351095A_ABST
    Figure CN119351095A_ABST
Patent Text Reader

Abstract

The invention discloses a high-brightness piezoelectric mechanical luminescent material with the chemical formula of LiNbO3: 0.01 Pr, xZn and a preparation method and application thereof, x is larger than 0 and smaller than or equal to 0.02, the preparation process is simple, and the prepared material has the mechanical luminescent characteristics of high brightness, long-term storage and repeatability, can be used as a mechanical luminescent material as a stress distribution visualization material, and can be applied to the field of light emitting devices. Or the optical anti-counterfeiting function can be realized as an anti-tamper label.
Need to check novelty before this filing date? Find Prior Art

Description

Technical field:

[0001] The present invention relates to the technical field of luminescent materials, and in particular to a high-brightness piezoelectric mechanical luminescent material and a preparation method and application thereof. Background technology:

[0002] Mechanical luminescence refers to the property of converting mechanical energy into light energy quantitatively under mechanical stimulation, wherein the mechanical stimulation includes crushing, friction, impact, compression, stretching, bending, twisting, ultrasound, etc. Mechanical luminescent materials with piezoelectric effect can realize the energy conversion of electrical energy-mechanical energy-light energy, and can be applied to the fields of triboluminescent anti-counterfeiting ink, flexible wearable materials, pressure detection sensors, disease monitoring and structural flaw detection (see, for example: HUANG ZF, et al. Smart mechanoluminescent phosphors: a review of strontium-aluminate-based materials, properties, and their advanced application technologies [J]. Adv. Sci., 2023, 10 (3): 2204925-1-44. XU CN, et al. Direct view of stress distribution in solid by mechanoluminescence [J]. Appl. Phys. Lett., 1999, 74 (17): 2414-2416.). The mechanoluminescent materials reported so far can be divided into three categories: organic, inorganic, and organic-inorganic hybrid materials. Among them, there are many types of organic mechanoluminescent materials, but they have the disadvantages of complicated and cumbersome synthesis process, low luminescence efficiency, poor thermal stability, and insufficient optical stability; while organic-inorganic hybrid mechanoluminescent materials have poor interface compatibility, low material stability, and it is difficult to optimize mechanical flexibility and luminescence performance at the same time, making it difficult to achieve effective utilization. Inorganic mechanoluminescent materials have problems such as single material type and low luminescence intensity. At present, the types of piezoelectric inorganic mechanoluminescent materials with high luminescence intensity, long-term storage and good repeatability are still relatively few, so there is an urgent need to develop more new and stable piezoelectric inorganic mechanoluminescent materials. Summary of the invention:

[0003] The purpose of the present invention is to provide a high-brightness piezoelectric mechanical luminescent material and a preparation method and application thereof.

[0004] The present invention is achieved through the following technical solutions:

[0005] A high brightness piezoelectric mechanical luminescent material with a chemical formula of LiNbO3:0.01Pr,xZn, wherein 0<x≤0.02, preferably 0.001≤x≤0.01, and most preferably x is 0.005.

[0006] The high brightness piezoelectric mechanical luminescent material is composed of Li2CO3, Nb2O5, Pr6O 11 and ZnO as raw materials through a high-temperature solid phase method, and the preparation method comprises the following steps: the raw materials are placed in an oven at 60-100°C and dried for 4-6 hours, the raw materials are accurately weighed according to the mass fraction of the required components of the chemical formula LiNbO3:0.01Pr,xZn and poured into an agate mortar, and ground with anhydrous ethanol as a medium for 15-20 minutes, and then the mixed raw materials are placed in an oven at 60-100°C and dried for 5 minutes; the dried raw materials are calcined at 1000-1100°C for 6-8 hours, naturally cooled to room temperature and ground again for 3-5 minutes to obtain the product.

[0007] The material prepared by the present invention has high-brightness, long-term storage and repeatable mechanical luminescence properties. It has mechanical luminescence emission after being irradiated with sunlight for 10 minutes or irradiated with 365nm ultraviolet light for 60 seconds during the period of 12:00-16:00, and the luminescence intensity is enhanced by 100% compared with the sample LiNbO3:0.01Pr without Zn doping. After being placed in a dark room environment for 30 days, it still has mechanical luminescence emission, and the process does not need to be irradiated again; it has good repeatability. Under sunlight irradiation or 365nm ultraviolet light irradiation during the period of 12:00-16:00, the mechanical luminescence intensity can be restored to the initial state, and the repeatability can be maintained for 5 cycles.

[0008] Therefore, the present invention also protects the application of the high-brightness piezoelectric mechanical luminescent material as a mechanical luminescent material used as a stress distribution visualization material, or as an optical anti-counterfeiting material such as an anti-tampering label.

[0009] When used, the high brightness piezoelectric mechanical luminescent material is compounded with a resin, which includes epoxy resin and the like.

[0010] A mechanical luminescent composite material comprises the high-brightness piezoelectric mechanical luminescent material and a resin, wherein the resin comprises epoxy resin or the like.

[0011] The beneficial effects of the present invention are as follows:

[0012] 1) The material prepared by the present invention has high brightness and can store mechanical luminescence properties for a long time. The mechanical luminescence intensity is enhanced by 100% compared with the sample LiNbO3:0.01Pr without Zn doping. It still has mechanical luminescence emission after being placed in a dark room for 30 days, and the process does not require re-irradiation.

[0013] 2) The mechanical luminescence property of the material prepared by the present invention has good repeatability. Under the re-irradiation of sunlight or 365nm ultraviolet light, the mechanical luminescence intensity can be restored to the initial state and the repeatability can be maintained for 5 cycles.

[0014] 3) The preparation process of the present invention is simple.

[0015] In summary, the preparation process of the present invention is simple, and the prepared material has high-brightness, long-term storage and repeatable mechanical luminescence properties. It can be used as a mechanical luminescence material for stress distribution visualization, or as an optical anti-counterfeiting material such as an anti-tampering label. Description of the drawings:

[0016] Figure 1 XRD patterns of LiNbO3:0.01Pr,xZn (x=0, 0.005, 0.01, 0.015) prepared in Examples 1-3 and Comparative Example 1;

[0017] Figure 2 Mechanical luminescence spectra of LiNbO3:0.01Pr,xZn (x=0, 0.005, 0.01, 0.015) prepared in Examples 1-3 and Comparative Example 1;

[0018] Figure 3 The mechanical luminescence change diagram of the sample of LiNbO3:0.01Pr,xZn (x=0.005) prepared in Example 1 after irradiation with 365nm ultraviolet light for 60s for 5 cycles;

[0019] Figure 4 The mechanical luminescence change diagram of the sample of LiNbO3:0.01Pr,xZn (x=0.005) prepared in Example 1 after 10 minutes of sunlight irradiation for 5 cycles;

[0020] Figure 5 Mechanical luminescence change diagram of LiNbO3:0.01Pr,xZn (x=0, 0.005, 0.01) prepared in Example 1-2 and Comparative Example 1 after being placed for 30 days;

[0021] Figure 6 Amplitude curves of LiNbO3:0.01Pr,xZn (x=0.005, 0.01) prepared for Example 1-2;

[0022] Figure 7 This is a luminescent image after the letter images "M" and "L" are written on the surface of the composite sample of the LiNbO3:0.01Pr, 0.005Zn material and epoxy resin prepared in Example 1 with a glass rod. Specific implementation method:

[0023] The following is a further description of the present invention, rather than a limitation of the present invention.

[0024] Example 1: Preparation and application of LiNbO3:0.01Pr,0.005Zn

[0025] Step 1) The raw materials used are Li2CO3 (purity 99.99%), Nb2O5 (purity 99.99%) and Pr6O 11 (purity 99.9%) and ZnO (purity 99.99%) were dried in an oven at 70 °C for 6 h;

[0026] Step 2) According to the mass fraction of the required components of the chemical formula LiNbO3:0.01Pr,xZn (x=0.005), the raw materials are accurately weighed and placed in an agate mortar, and ground with anhydrous ethanol for 15 minutes, and then the mixed raw materials are placed in an oven at 70°C and dried for 5 minutes;

[0027] Step 3) The dried product is sintered at 1080°C for 8 hours, cooled naturally to room temperature and ground again for 5 minutes to obtain LiNbO3:0.01Pr,xZn (x=0.005) mechanical luminescent material that can be stored for a long time and has good repeatability.

[0028] The sample prepared in Example 1 was subjected to XRD test, and the test results are as follows: Figure 1 As shown, LiNbO3:0.01Pr,0.005Zn is a single-phase material, which matches the standard card (PDF#85-2456), and no other impurity phases and secondary phases are produced, proving that LiNbO3:0.01Pr,0.005Zn was successfully prepared.

[0029] In addition, in order to characterize mechanical luminescence, the prepared material needs to be compounded with epoxy resin through a mold to obtain a mechanical luminescent composite material. The compounding steps are:

[0030] Step 1) Prepare an epoxy resin mixture, pour 3g of epoxy resin A glue (TJ 2221A, Trulli (Suzhou) Material Technology Co., Ltd.) and 1g of epoxy resin B glue (TJ 2221B, Trulli (Suzhou) Material Technology Co., Ltd.) into a culture dish at a mass ratio of 3:1, and stir with a glass rod to mix them evenly without generating bubbles;

[0031] Step 2) Weigh 1.5 g of the mechanical luminescent material powder in Example 1 above, add it into a mold, press it lightly, and evenly spread it on the bottom of a polytetrafluoroethylene mold (inner diameter 25 mm);

[0032] Step 3) Add the mixed epoxy resin mixture into the mold and let it stand at room temperature for 3 minutes;

[0033] Step 4) The material after standing is placed in a 70° C. oven for 4 hours, and then demolded to obtain a bulk mechanical luminescent composite material.

[0034] In order to prove that LiNbO3:0.01Pr,0.005Zn has mechanical luminescence performance, mechanical luminescence spectrum test was carried out. The test results are as follows Figure 2 As shown, the bulk mechanoluminescent composite material prepared in Example 1 exhibits Pr 3+ The characteristic emission band of the present invention is 616 nm, and the maximum emission band is 616 nm. The test results show that the material of the present invention exhibits an immediate and strong mechanical luminescence signal.

[0035] In order to prove the repeatability of the mechanoluminescence performance of LiNbO3:0.01Pr,0.005Zn, a mechanoluminescence cycle test was carried out. The test results are shown in Figure 2. Figure 3 As shown, before the test, the bulk mechanoluminescent composite material prepared in Example 1 was irradiated with 365nm ultraviolet light for 60s only once, a mechanical force of 30N was applied, and the mechanoluminescence spectrum was tested continuously for 5 cycles; in addition, before each test, it was irradiated with 365nm ultraviolet light for 60s, and a mechanical force of 30N was also applied, and the mechanoluminescence spectrum was tested continuously for 5 cycles. The test results show that under 5 consecutive cycles of testing, when the test process was not irradiated with 365nm ultraviolet light again, the mechanoluminescence intensity showed a trend of gradually weakening; when the test was irradiated with 365nm ultraviolet light again before the test, the mechanoluminescence intensity could be restored to the initial value. The material of the present invention exhibits good repeatability in mechanoluminescence performance.

[0036] In order to prove the repeatability of the mechanoluminescence performance of LiNbO3:0.01Pr,0.005Zn, a mechanoluminescence cycle test was carried out. The test results are shown in Figure 2. Figure 4 As shown, the bulk mechanoluminescent composite material prepared in Example 1 was irradiated with sunlight for only 10 minutes once before the test, and a mechanical force of 30N was applied, and the mechanoluminescence spectrum was tested continuously for 5 cycles; in addition, it was irradiated with sunlight for 10 minutes before each test, and a mechanical force of 30N was also applied, and the mechanoluminescence spectrum was tested continuously for 5 cycles. The test results show that under 5 consecutive cycles of testing, when the test process was not irradiated with sunlight again, the mechanoluminescence intensity showed a trend of gradually weakening; when it was irradiated with sunlight again for 10 minutes before the test, the mechanoluminescence intensity could be restored to the initial value. The material of the present invention exhibits good repeatability in mechanoluminescence performance.

[0037] In order to prove that the mechanoluminescence of LiNbO3:0.01Pr,0.005Zn can be stored for a long time, mechanoluminescence tests were carried out after different storage times. The test results are shown in the figure. Figure 5As shown, the bulk mechanoluminescent composite material prepared in Example 1 was irradiated with 365nm ultraviolet light for 60s only in the first test. The test process was stored in a dry darkroom environment. With the increase of placement time, the mechanoluminescence intensity showed an obvious attenuation trend. After being placed for 30 days, a 30N mechanical force was applied and obvious mechanoluminescence signals were still generated, which was visible to the naked eye. The material of the present invention showed good mechanoluminescence performance after long-term storage.

[0038] In order to prove that the LiNbO3:0.01Pr,0.005Zn material has piezoelectricity, an amplitude curve test was carried out. The test results are as follows Figure 6 As shown, the material prepared in Example 1 shows a typical butterfly amplitude curve under the action of an external electric field, and when a voltage of 9 V is applied, the amplitude is 73.16 pm. The material of the present invention has piezoelectric properties.

[0039] After the LiNbO3:0.01Pr,0.005Zn material prepared in Example 1 of the present invention was compounded with epoxy resin, the letter images of "M" and "L" were written on the surface of the composite sample with a glass rod. The luminescent image is as follows: Figure 7 As shown, it proves its value as a material for visualizing stress distribution.

[0040] Example 2: Preparation and application of LiNbO3:0.01Pr,xZn (x=0.01):

[0041] Refer to Example 1, except that: the required component mass fraction of step 2) satisfies the chemical formula LiNbO3:0.01Pr,xZn (x=0.01).

[0042] The samples prepared in Example 2 were subjected to XRD test, and the test results are as follows: Figure 1 As shown, it is proved that the LiNbO3:0.01Pr,0.01Zn material was successfully prepared.

[0043] The mechanical luminescence test method of LiNbO3:0.01Pr,0.01Zn, a piezoelectric mechanical luminescence material that is long-term storable and repeatable, is the same as that in Example 1.

[0044] The composite material prepared in Example 2 exhibits a Pr 3+ The characteristic emission band of the invention has a maximum emission band at 616 nm. The test results show that the material of the invention exhibits obvious mechanical luminescence signals. The test results are as follows Figure 2 shown. Figure 5The graph shows the change of mechanical luminescence at different storage times. As the storage time increases, the mechanical luminescence intensity shows a clear attenuation trend. After 30 days of storage, a 30N mechanical force is applied, and a clear mechanical luminescence signal can still be generated. The material of the present invention shows good mechanical luminescence performance after long-term storage. The material prepared in Example 2 shows a typical butterfly amplitude curve under the action of an external electric field. When a voltage of 9V is applied, the amplitude is 74.62pm, showing piezoelectric properties. The test results are shown in FIG. Figure 6 As shown, the test method is the same as that in Example 1.

[0045] Example 3: Preparation and application of LiNbO3:0.01Pr,xZn (x=0.015):

[0046] Refer to Example 1, except that the mass fraction of the required components in step 2) satisfies the chemical formula LiNbO3:0.01Pr,xZn (x=0.015). XRD test was performed on the sample prepared in Example 3, and the test results are as follows: Figure 1 As shown, it is proved that the LiNbO3:0.01Pr,0.015Zn material was successfully prepared.

[0047] LiNbO 3: The mechanical luminescence test method of the piezoelectric mechanical luminescent material with 0.01Pr, 0.015Zn and long-term storage and repeatability is the same as that in Example 1.

[0048] The composite material prepared in Example 3 exhibits a Pr 3+ The characteristic emission band of the invention has a maximum emission band at 616 nm. The test results show that the material of the invention exhibits obvious mechanical luminescence signals. The test results are as follows Figure 2 As shown, the testing method is the same as that in Example 1.

[0049] In order to study the effect of Zn doping amount on the brightness, storage and repeatability of mechanical luminescent materials, the material prepared by Comparative Example 1 was obtained.

[0050] Comparative Example 1: Preparation method of LiNbO3:0.01Pr

[0051] Refer to Example 1, except that: the mass fraction of the required components in step 2) satisfies the chemical formula LiNbO3:0.01Pr,xZn (x=0). XRD test was performed on the sample prepared in Comparative Example 1, and the test results are as follows: Figure 1 As shown, it is proved that the LiNbO3:0.01Pr material was successfully prepared.

[0052] The composite material prepared in Comparative Example 1 exhibited a Pr 3+The characteristic emission band of the invention has a maximum emission band at 616nm. The test results show that the material of the invention exhibits a relatively weak mechanical luminescence signal. The test results are as follows Figure 2 As shown, the testing method is the same as that in Example 1. Figure 5 The figure shows the change of mechanical luminescence at different storage times. As the storage time increases, the mechanical luminescence intensity shows an obvious attenuation trend. After 30 days of storage, a mechanical force of 30N is applied, and a weak mechanical luminescence signal is detected, which is difficult to observe with the naked eye. After long-term storage, the mechanical luminescence performance of LiNbO3:0.01Pr is difficult to detect.

[0053] In the above examples, the mechanical luminescence brightness of the sample prepared in Example 1 is the strongest and can be stored for a long time. After 30 days of storage, the mechanical luminescence signal is strong and can be observed by the naked eye, with good repeatability. Therefore, it is preferably 0.001≤x≤0.01 and most preferably x is 0.005.

Claims

1. A high brightness piezoelectric mechanical luminescent material with a chemical formula of LiNbO3:0.01Pr,xZn, wherein 0<x≤0.

02.

2. The high brightness piezoelectric mechanical luminescent material according to claim 1, characterized in that: 0.001≤x≤0.01。 3. The high brightness piezoelectric mechanical luminescent material according to claim 1, characterized in that: The high brightness piezoelectric mechanical luminescent material is composed of Li2CO3, Nb2O5, Pr6O 11 It is prepared by a high temperature solid phase method using ZnO as raw materials.

4. The high brightness piezoelectric mechanical luminescent material according to claim 1, characterized in that: The preparation method comprises the following steps: The raw materials are placed in an oven at 60-100°C for drying for 4-6 hours, and the raw materials are accurately weighed according to the mass fraction of the required components of the chemical formula LiNbO3:0.01Pr,xZn and poured into an agate mortar, and ground with anhydrous ethanol as a medium for 15-20 minutes, and then the mixed raw materials are placed in an oven at 60-100°C for drying for 5 minutes; the dried raw materials are calcined at 1000-1100°C for 6-8 hours, naturally cooled to room temperature, and then ground again for 3-5 minutes to obtain the product.

5. The method for preparing the high-brightness piezoelectric mechanical luminescent material according to claim 1, characterized in that: The following steps are involved: The raw materials are placed in an oven at 60-100°C for drying for 4-6 hours, and the raw materials are accurately weighed according to the mass fraction of the required components of the chemical formula LiNbO3:0.01Pr,xZn and poured into an agate mortar, and ground with anhydrous ethanol as a medium for 15-20 minutes, and then the mixed raw materials are placed in an oven at 60-100°C for drying for 5 minutes; the dried raw materials are calcined at 1000-1100°C for 6-8 hours, naturally cooled to room temperature, and then ground again for 3-5 minutes to obtain the product.

6. The use of the high brightness piezoelectric mechanical luminescent material according to claim 1, characterized in that: It can be used as a mechanical luminescent material to visualize stress distribution, or as an optical anti-counterfeiting label for tamper-proofing.

7. The use according to claim 6, characterized in that: High brightness piezoelectric mechanical luminescent material and resin composite.

8. The use according to claim 7, characterized in that: The resin is epoxy resin.

9. A mechanical luminescent composite material, comprising the high-brightness piezoelectric mechanical luminescent material and a resin.

10. The mechanoluminescent composite material according to claim 9, characterized in that: The resin is epoxy resin.

Citation Information

Patent Citations

  • Heterostructure material capable of realizing repeated stress luminescence and preparation method thereof

    CN113355094A

Cited By

  • Visual mechanical luminescent ceramic, preparation method and application in grain mechanical equipment detection

    CN120172736A

  • LiNbO3-based material with enhanced red and high-penetration near-infrared mechanical luminescence properties as well as preparation method and application of LiNbO3-based material

    CN121628628A